Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 11 - Section 11.1 - Solving Quadratic Equations by Completing the Square - Exercise Set: 36

Answer

$y=(-4,-2)$

Work Step by Step

Step -1 : Add the square of half of the co-efficient of $y$ to both sides. Co-efficient of $y = 6$ Half of $6 = \frac{1}{2}×6=3$ Square of $3$ is $3×3=9$ The equation becomes $y^2+6y+9=-8+9$ Step-2 Factor the trinomial and simplify the right hand side. $(y+3)^2=1$ Step-3 Use the square root property and solve for $y$ $(y+3)=±\sqrt 1$ $y+3=±1$ Step-4 Subtract 3 on both the sides $y=−3±1$ Therefore the solution set is $(-4,-2)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.